Influence of socio-demographic factors in the promotion of social entrepreneurship: A service-learning programme - Maravé-Vivas, María; Salvador-García, Celina; Capella-Peris, Carlos; Gil-Gómez, Jesús (MDPI, 2022)
Social entrepreneurship (SE) is often presented in the literature as the key to solve many of this world’s persistent social problems. SE offers a special opportunity to address the 2030 Agenda for Sustainable Development and to boost the Sustainable Development Goals (SDGs). This research examines the effects of Service Learning (SL) on the SE of university students and to examine whether certain sociodemographic factors (i.e., age, entrance studies, family studies, social participation, and employment situation) are associated with students’ SE competence development when applying SL. Pre-service teachers (n = 98) of the degree in early childhood education applied a physical education SL programme. We used a quantitative method with a pre-experimental design, using pre-test and post-test measures. The findings obtained show a significant improvement on the SE competence of PSTs, so SL seems a good tool to develop it. The results that analyse the influence of socio-demographic factors do not show significant correlations. There are very few studies focusing on this objective, so it would be interesting to encourage the research community to provide more data in this area.
Keywords: active methodology; higher education; physical education; service-learning; social entrepreneurship; Scopus; JCR